Analisis faktor-faktor determinan Individu terhadap Tuberculosis Multidrug Resistant (TB MDR) di Provinsi Sumatera Selatan - Nugi Nurdin (Jurnal Kesehatan Komunitas, 2020)
Background: "Multidrug resistant tuberculosis (MDR TB) is one type of tuberculosis resistance against at least two first line tuberculosis antibiotic drugs, namely INH and Rifampicin with or not resistant to other tuberculosis antibiotic drugs". MDR TB is a health problem for the world community, including in Indonesia which causes many deaths. This study was conducted to look for the causal factors for the incidence of MDR TB.Met The design of this study used case control with mixed methods. Data collection is done by interviewing using questionnaires, directed discussions, in-depth interviews and observations. Data measurement in this study used bivariate logistic regression.Conclusion: Determinants of the incidence of MDR TB are education, history of TB disease, results of failed TB treatment, history of dropping out of treatment, TB patients with diabetes mellitus and TB patients who have difficult access to health facilities